REPRODUCCIÓN SOCIAL EN EL RENDIMIENTO DE ESTUDIANTES EN LA EDUCACIÓN SUPERIOR. CASO DE LA UNIVERSIDAD NACIONAL, COSTA RICA - Rodríguez Pineda, Magaly; Artavia Aguilar, Cindy Vanessa (Universidad de Costa Rica, 2021)
The subject of this research is centred in demonstrating whether a higher economic and cultural capital implies a better academic performance. As a theoretical framework, the study applies Pierre Bourdieu and Jean-Claude Passeron’s Social Reproduction Theory, as presented in 1972 by the French sociologists in their work entitled Reproduction in Education, Society and Culture. The operationalization was conducted using a multiple regression model. The results demonstrated that the students with higher academic performance come from districts with a medium or high Social Development Index, meaning they are able to commit full-time to their studies. Moreover, they come from homes consisting of a head of household and a spouse, with a positive learning environment and adequate structural conditions.